(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Hermeneutics is faced with the challenge of Legal IT control. The structure ofthe IT system fosters the tendency of mechanical or automated justice, allowing cyberlaw to become established, thus completely disregarding all Hermeneutic operations.The problem arises in data banks use and this is a case where restraint and reflectionby the administrator is required. IT facilitates quantitative information growth, butthis requires the person interpreting such to resort to certain arguments and reasoningin order to overcome imitation or even the copy of unrelated repeated speechwithout professional accountability.